The cheese - Palatini, Margie; Johnson, Steve, 1960-; Fancher, Lou (New York, NY : Katherine Tegen Books, 2007)
After they all agree to ignore the story of "The Farmer in the Dell," the rat, cat, dog, child, farmer, and his wife have a party featuring the tempting hunk of cheese.
Preschool-2.
Accelerated Reader/Renaissance Learning
A Junior Library Guild selection
Keywords: Nursery rhymes; Characters and characteristics in literature -- Fiction; Humorous stories; Humorous stories; Picture books for children